Level of natremia as an index of the condition of the organism of animals under stress - Zaprudnova, R. A. (Regulatory Mechanisms in Biosystems, 2021)
In the diagnosis of stressful conditions in humans and other animals, ionic indicators remain practically unused. In this work, we studied the changes in the concentrations of sodium ions in the blood plasma of freshwater fish under stress caused by stressors of different quality and quantity. Most of the experiments were carried out on adult bream (Abramis brama L) from the Rybinsk Reservoir. Separate experiments were duplicated on adult individuals of roach (Rutilus rutilus L.), pike (Esox lucius L.), and blue bream (Abramis ballerus L.). The concentration of cations in the blood plasma was determined using a Flapho-4 flame photometer. Under the action of mild and short-term stressors of different qualities, the sodium concentration in the internal environment altered toward an increase in concentration gradients on the cell membrane (eustress or physiological stress). Hypernatremia was approximately 10%. Under the action of strong and/or prolonged stressors of different strength, the sodium concentration in the internal environment changed toward a decrease in concentration gradients on the cell membrane (distress or pathological stress). Hyponatremia was 50% in the conditions of acute lethal stress, 20% in subacute lethal stress, 10% or more in chronic lethal stress. During strong acute reversible stress, hyponatremia could reach 30%. Analysis of the material on mammals allowed us to conclude that the adaptation mechanisms in fish and higher vertebrates are similar. In this work, for the first time, the state of the system of electrolyte balance of animals under stress was analyzed from the standpoint of the leading role of ionic concentration gradients on the cell membrane (mainly sodium) in the energetics (level of disequilibrium) of the organism. We propose a concept that in normal and extreme conditions fish use two different defense reactions (or adaptation strategies): active and passive, consisting, respectively, in increasing or decreasing the level of disequilibrium (energy) in the organism. The hyponatremia recorded by numerous authors, which accompanies diseases in humans, is evidently a nonspecific reaction of the organism and serves as an indicator of reduced energy of the organism. It is suggested that the sodium level in the internal environment of the organism be used for diagnosing the stress state of animals.